Database modeling & design logical design - Teorey, Toby J.; Lightstone, Sam.; Nadeau, Tom, 1958- (Amsterdam : Elsevier ; Boston : Morgan Kaufmann Publishers, 2006)
Database systems and database design technology have undergone significant evolution in recent years. The relational data model and relational database systems dominate business applications; in turn, they are extended by other technologies like data warehousing, OLAP, and data mining. How do you model and design your database application in consideration of new technology or new business needs? In the extensively revised fourth edition, you'll get clear explanations, lots of terrific examples and an illustrative case, and the really practical advice you have come to count on--with design rules that are applicable to any SQL-based system. But you'll also get plenty to help you grow from a new database designer to an experienced designer developing industrial-sized systems: a detailed look at the Unified Modeling Language (UML-2) as well as the entity-relationship (ER) approach for data requirements specification and conceptual modeling--with examples throughout the book in both approaches; the details and examples of how to use data modeling concepts in logical database design, and the transformation of the conceptual model to the relational model and to SQL syntax; the fundamentals of database normalization through the fifth normal form; practical coverage of the major issues in business intelligence--data warehousing, OLAP for decision support systems, and data mining; examples for how to use the most popular CASE tools to handle complex data modeling problems; exercises that test understanding of all material, plus solutions for many exercises.
The entity-relationship model -- The unified modeling language (UML) -- Requirements analysis and conceptual data modeling -- Transforming the conceptual data model to SQL -- Normalization -- An example of logical database design -- Business intelligence -- CASE tools for logical database design.
Includes bibliographical references and index.
Keywords: Relational databases; Database design; Electronic books